Make 6 5 4 3 = 1

Can you find a way to make:

6 5 4 3 = 1

by concatenation and/or adding any of (and only) these mathematical operators:

• +
• -
• ×
• !
• ÷
• ^
• standard parentheses ()

You cannot add other numbers to the equation.
The result must be a mathematical equality.

Inspired by Make 5 5 5 5 = 19

• Yep, I totally failed to see the obvious! Hopefully 6 5 4 3 = 81 will be more fun. Aug 27, 2018 at 6:25
• Chill Everyone! Stop Downvoting Just Becasue it's obvious +1
– user44188
Aug 28, 2018 at 6:11
• I can do $6\; 5 \;4\; 3\; 2 = 1$ by how $4!\div (6\times (5-3)\times 2) = 1$ :D Aug 28, 2018 at 14:03
• I can also complete it without the $6$ by how $(4!-3!)\div 5!! = 1$ :D Aug 29, 2018 at 22:10

(6 - 5) * (4 - 3)

By request another:

-(6 + 5) + (4 * 3)

(6 - 5)! * (4 - 3)!
(6 - 5) ^ (4 - 3)
(6 - 5) / (4 - 3)
(6 - 5)! / (4 -3)!
plus other combinations of factorials of 1

Another solution:

6 + 5 - 4 - 3!

More complicated:

(6!) / (5 * 4! * 3!)

• Nice and simple one... any more? :) Aug 27, 2018 at 5:38
• Ho hum. I epic fail :D guess I'll try again... Aug 27, 2018 at 5:41
• Should I go on? Aug 27, 2018 at 5:47
• LOL, see my previous comment Aug 27, 2018 at 6:04
• @wolfram42 Yes, please go on there ;-) Aug 28, 2018 at 14:23

I'm going to try:

$$\dfrac{-6+5+4}{3}=1$$

and:

$$\dfrac{6\times5}{4!+3!}=1$$

The simplest:

$65 - 4^3$

(I wrote a program.)

Some exponential solutions

$\frac{6^{5-4}}{3!}$
$(6 - 5^{4-3})$

A simple solution

${3 - \dfrac{6 + 4}{5}}$

In code form

3 - (6 + 4)/5

Very simple.

(6-5)*4-3
6-5=1 => 1*4=4 => 4-3=1

Cannot get simpler than this.

• Hello and welcome to PSE! Please hide your answers in spoilers using the >! prefix on the lines needing hiding. Aug 29, 2018 at 13:12
• sure will do from now.. Thanks for letting me know! Aug 30, 2018 at 3:54

Simple and in order:

(6 - 5 - 4 + 3)!

Here are some solutions I found:

• (6-5)^(4-3)
• (6-5)*(4-3)
• (6-5)/(4-3)
• (6+5)-(4+3!)
• (6+5)+(4*3)
... way too many!

• Hello, and welcome to PSE! Unfortunately your answer doesn't add anything new to the existng ones (wolfram42 already gave the same answers like you did). Anyways, feel free to stick around, check out the Tour and enjoy your stay at the site! Sep 11, 2018 at 20:54

Assuming the following is possible:

(6+5)->(11)->(1+1)

then: 1)

((6+5)-4)+3)=1

2)

((11)-(4)+3)=1

3)

((1+1)-(4)+3)=1

4)

(2-4)+3=1

Here is another one:

((6*5)-4!)/3!